2019
DOI: 10.1111/rda.13470
|View full text |Cite
|
Sign up to set email alerts
|

Red‐light stimulation of boar semen prior to artificial insemination improves field fertility in farms: A worldwide survey

Abstract: A survey of in vivo fertility data from 31 pig farms distributed worldwide was conducted to determine whether stimulating boar semen with LED‐based red light increases its reproductive performance following artificial insemination (AI). Red‐light stimulation with MaXipig® was found to increase farrowing rates (mean ± SEM, control: 87.2% ± 0.4% vs. light stimulation 90.3% ± 0.5%) and the number of both total and live newborn piglets. Red‐light stimulation increased farrowing rates in 27 farms, with an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Studies conducted with pig semen have reported that reproductive performance can be increased through light-stimulation of semen prior to AI [ 7 , 8 ]. In effect, previous works using different light sources, such as lasers and light-emitting diodes (LED), have suggested that light-stimulation has a positive effect on the motility and ability of sperm to fertilize the oocyte in pigs [ 7 , 8 , 9 ], mice [ 10 ], and sheep [ 11 ]. Remarkably, no study has reported any detrimental effect of visible light on DNA integrity [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted with pig semen have reported that reproductive performance can be increased through light-stimulation of semen prior to AI [ 7 , 8 ]. In effect, previous works using different light sources, such as lasers and light-emitting diodes (LED), have suggested that light-stimulation has a positive effect on the motility and ability of sperm to fertilize the oocyte in pigs [ 7 , 8 , 9 ], mice [ 10 ], and sheep [ 11 ]. Remarkably, no study has reported any detrimental effect of visible light on DNA integrity [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among all visible light spectra tested, red-light has been shown to be the one that improves sperm motility the most [ 15 ]. In addition to this, it has been reported that red-light stimulation (620–630 nm) by LED increases the fertilizing ability of pig sperm [ 7 , 8 , 9 ], without affecting their viability [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the studies, performed in (20), seem most impressive. An analysis of in vivo fertility data from 31 pig farms distributed worldwide with more than 33 thousand sows involved was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies performed with sperm from different species have shown that the radiation in visible spectral region (blue-green region: k = 470 nm (13), green: k = 532 nm (25,39), k = 490-540 nm (34); red: k = 620-630 (2,(20)(21)(22)(23), k = 630 (19), k = 632.8 (15,24,27,28,30,35,36), k = 635 nm (38), k = 637 nm (14), k = 647 nm (1), k = 650 nm (35), k = 655 nm (30,31), k = 660 nm (26,29), k = 670 nm (37)) and in near-infrared spectral region (k = 810 nm (16,19), k = 830 nm (12), k = 850 nm (14), k = 905 nm (11), k = 940 nm (10)), as well as broadband white light (k = 400-800 nm (17,18,27)), exerts a regulatory effect on spermatozoa.…”
Section: •-mentioning
confidence: 99%
See 1 more Smart Citation